Are Islamic incomes relevance to commercial banks in Malaysia? - Cheng, Fan Fah; Md Nasir, Annuar (David Publishing Company, 2010)
A significant price-to-earnings relation is evident in many research findings, which includes study on Malaysia Stock Markets, that the strength, consistency and magnitude of the relation are not as large as those reported in institutionally more developed markets. However, the price adjustment is stronger if price reaction is measured over a long periods, which is consistent to speculative trading. Firm-specific variables such as revenue, firm size and debt-equity have no incremental information content beyond earnings implies that the market monitoring process in an emerging market focuses on earnings only during financial announcement. Therefore, this paper revisited the study on the relevant of accounting earnings by looking at Islamic Income for commercial banks in Malaysia using the earnings response coefficients, which are the earnings-to-share return coefficients that are estimated for sub earnings components by including Islamic banking incomes in the analysis. This paper discovered that though there is a positive effect, the earnings from Islamic banking operation are small. Thus, the total earnings as well as the sub-categories of earnings of banks appear to enter the pricing considerations of investors.